Profesor Tadeusz Skulina – historyk języka i onomasta - Pihan-Kijasowa, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
Professor Tadeusz Skulina (1929–1992) was born in Katowice but from the Second World War he was connected with Great Poland. Also in Poznań, he studied Polish Studies and following his graduation became employed at Adam Mickiewicz University in Poznań where he completed the consecutive stages of his scholarly career. As a disciple of Professor Władysław Kuraszkiewicz he conducted research on the Polish language of the Old-Polish era and of the 16th century. His doctoral thesis (1964) was devoted to historical phonetics and historical dialectology but soon he changed his scholarly interests and entered the field of Slavic studies, especially East-Slavic languages. In his habilitation thesis he discussed the question of the Old-Ruthenian anthroponymy. This thesis, published in 1973, was the first original, so extensive and detailed thesis about the Old-Ruthenian names. As we know, in the period following the receipt of his habilitation degree Professor Tadeusz Skulina had plans to prepare a monograph about Polish feminine onomastics. He had pursued this for years, however, unfortunately, never managed to prepare a synthesis. He only left an unfinished editorial draft of this book. Apart from research activities, Professor Skulina was involved in didactics and also performed responsible administrative functions at the Institute of Polish Philology, was a member of numerous scholarly societies. For his achievements, he received many awards and honours. Professor Tadeusz Skulina died in 1992 after a long and emaciating illness. The scholarly achievements he has left inspire the successive generations of researchers. He also left unfinished written works and ideas which he never managed to realize.